2008
DOI: 10.3171/spi.2008.9.10.354
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transnasal decompression for management of basilar invagination in osteogenesis imperfecta

Abstract: Osteogenesis imperfecta (OI) is a disorder of bone development caused by a genetic dysfunction of collagen synthesis. Basilar invagination (BI) is an uncommon but serious complication of OI. Brainstem decompression in OI is undertaken in certain circumstances. Transoral-transpalatopharyngeal ventral decompression with posterior occipitocervical fusion has become the treatment of choice when required. This technical note outlines a novel endoscopic transnasal approach for ventral decompression. The lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…11,12,17,18,26,30,31 There also have been reports about using ETO in pediatric and elderly patients. 12,19,28 Unlike the technique used in these other published cases, which uniformly involved a U-shaped mucosal flap, we used a linear vertical mucosal incision in the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,17,18,26,30,31 There also have been reports about using ETO in pediatric and elderly patients. 12,19,28 Unlike the technique used in these other published cases, which uniformly involved a U-shaped mucosal flap, we used a linear vertical mucosal incision in the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
“…1,24 In the past several years, there also have been case reports of ETO published by several authors worldwide. 3,7,11,12,17,18,28,30,31,37,39,40 However, reports on a series of consecutive patients who underwent ETO and long-term follow-up, including data on radiological and clinical outcomes and complications, are still scarce.The present study is, to date, the largest series reported on purely endoscopic transnasal resection of the odontoid process. The aim of this article is to describe the evolution of our surgical techniques for ETO and the outcomes in our series of patients.…”
mentioning
confidence: 99%
“…Serious complications documented in previous case reports and clinical series 3,[9][10][11][12]14,16,17,25,26,30,31,34 are infrequent. However, maintaining the integrity of the dura mater is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 3,[9][10][11][12]14,16,17,22,25,26,30,31,34 have demonstrated the effectiveness and feasibility of an odontoidectomy performed using an EEA and suggest the possibility of less invasiveness than with the oral or cervical approaches. In our small series there is no evidence of different neurological functional outcomes between the techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation